The ties that bind? Online musicians and their fans. Issue 2 (13th April 2015) - Daellenbach, Kate; Kusel, Rachael; Rod, Michel
Abstract : Purpose: – The purpose of this study is to examine the relationships between musician's social network sites (SNS), the tie that fans may develop via these sites, and music acquisition, via legal and illegal means. Design/methodology/approach: – A quantitative approach was taken, gathering 352 responses from young adults via an online survey. Findings: – Perceptions of interactivity and sincerity on musicians' SNS are found to lead to stronger ties, enhancing the fan's feeling of closeness to the musician, the fan's inclination to spread positive word-of-mouth, and the time a fan spends on the site. Pathways are found between the fan activity, sense of closeness and time spent on the SNS. In terms of acquisition, the tie strength indicator of time spent on the SNS holds a positive relationship with purchase intent. While a sense of closeness holds a negative relationship to illegal downloading activity, the fan's activity recommending the musician has a positive influence on illegal downloading. Research limitations/implications: – Limitations of this study include a limited amount of information on the musician and extent of fandom, suggesting future research to tease out the effects of SNS on fans with varying levels of existing commitment to musicians. Practical implications: – Stronger ties between fans and musicians may be developed via interactive and sincere SNS. Activities which encourage the fan to give recommendations and spread positive word-of-mouth are especially influential in driving purchase intent. Originality/value: – These results provide theoretical and practical implications in relation to how SNS may influence the online fan-celebrity "tie" and music acquisition – three elements which have not to date been examined.